PREDICTIVE RELATIONSHIP BETWEEN MATHEMATICAL REFLECTIVE THINKING AND MATHEMATICAL LITERACY AMONG PROSPECTIVE TEACHERS - Reni Nuraeni; Rizky Rosjanuardi; Al Jupri; Elah Nurlaelah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2026)
This study examines the predictive relationship between mathematical reflective thinking and mathematical literacy among prospective mathematics teachers, an area that remains relatively underexplored in teacher education research. Reflective thinkingÂ  is closely associated with higher-order cognitive and metacognitive processes that may support individuals in formulating, interpreting, and evaluating mathematical ideas in contextual situations. Therefore, this study aims to investigate the extent to which mathematical reflective thinking predicts mathematical literacy among prospective mathematics teachers. A quantitative correlational design was employed involving 30 prospective mathematics teachers from a private university in Garut Regency, Indonesia, selected through purposive sampling. Data were collected using mathematical reflective thinking and mathematical literacy tests developed based on Dewey’s reflective thinking indicators and PISA mathematical literacy frameworks. The instruments underwent expert validation involving five mathematics education experts and statistical validity and reliability testing. Simple linear regression analysis revealed a statistically significant predictive relationship between reflective thinking and mathematical literacy (t = 3.507, p = 0.002). Reflective thinking explained 30.5% of the variance in mathematical literacy (R2 = 0.305), indicating that although reflective thinking contributes substantially, other factors may also influence mathematical literacy development. These findings suggest that strengthening reflective thinking skills may support the enhancement of mathematical literacy among prospective mathematics teachers and provide implications for instructional design and teacher education practices.